PENGEMBANGAN E-MODUL STRUKTUR ATOM MENGGUNAKAN KVISOFT FLIPBOOK MAKER UNTUK KELAS X SMA/MA - Fatma, Eltarizky; Susilawati, Susilawati; Linda, Roza (Jurnal Tadris Kimiya, 2024)
Based on the results of interviews with several chemistry teachers, it was found that technology-based teaching materials still needed to be improved, especially regarding atomic structure material. Therefore, it is necessary to create technology-based learning materials. This study aims to develop an e-module of atomic structure material using Kvisoft Flipbook Maker software and determine the level of validity, practicality, and students' responses. This article was a type of Research and Development (R&D) using the Borg & Gall model. The research subjects were material, media, and educational practitioner experts as validators and students as the subjects of the feasibility tests. Data collection techniques included validity test questionnaires, practicality tests, students' responses to the test, interviews, and documentation. Data analysis used qualitative and quantitative analysis techniques. The research results show that the e-module validity level is 88.88% with a valid category for material and 93.16% with a valid category for media. The level of practicality obtained was 89.33% in the practical category. Apart from that, student responses obtained a score of 86.55% in the good category. Thus, the atomic structure e-module developed is valid, practical, and has received a good response.